Production of yeast biomass and cell wall to obtain β glucans for a biotechnological purpose - Pereyra, Carina Maricel (2020)
Taking into account that the composition of the yeast cell wall can vary with respect to different growth conditions, the objective of this study was to determine the influence of additives (EDTA, SDS, NaCl) on the production of yeast biomass, the percentage of cell wall and its composition, in order to obtain β-glucan. The extraction of the cell wall was carried out by an alkaline extraction technique and the study of the composition was carried out using infrared (IR) spectroscopy. The production of biomass and cell wall was variable, depending on the strain and the treatments studied. The IR spectra of each cell wall showed 3 characteristic regions of the wall (polysaccharides, proteins and lipids). In addition, it was possible to determine the chemical groups corresponding to beta glucans and amides I and II corresponding to chitin. The glucans content, and the β-glucan/chitin ratio in particular, varied with the yeast strain and with the additive studied. Future studies must be performed to extract the β-glucans and determine their concentration in each cell wall The optimization of the production of cell wall and its components from yeast strains will allow its application in obtaining β-glucans for the food, pharmacological and cosmetic industries.